1996
DOI: 10.1021/jm9603779
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relationships in a Series of Substituted Indolocarbazoles:  Topoisomerase I and Protein Kinase C Inhibition and Antitumoral and Antimicrobial Properties

Abstract: A series of compounds structurally related to staurosporine, rebeccamycin, and corresponding aglycones was synthesized, and their activities toward protein kinase C and topoisomerases I and II were tested together with their in vitro antitumor efficiency against murine B16 melanoma and P388 leukemia cells. Their antimicrobial activities were also examined against a Gram-negative bacterium (Escherichia coli), a yeast (Candida albicans), and three Gram-positive bacteria (Bacillus cereus, Streptomyces chartreusis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
72
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 121 publications
(81 citation statements)
references
References 21 publications
8
72
1
Order By: Relevance
“…The syntheses of the indolocarbazole R-3 and its aglycone derivative, R-4, have been reported previously (Rodrigues-Pereira et al, 1996). In the dry state, the drugs were stored in a desiccator in the dark at 4°.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The syntheses of the indolocarbazole R-3 and its aglycone derivative, R-4, have been reported previously (Rodrigues-Pereira et al, 1996). In the dry state, the drugs were stored in a desiccator in the dark at 4°.…”
Section: Methodsmentioning
confidence: 99%
“…We found that the presence of chlorine on the indolocarbazole chromophore (as in rebeccamycin) significantly reduces the effect on topoisomerase I, whereas the substituents on the maleimido function and the functional group on the nonindolic moiety can be varied without loss of activity. In addition, we showed that the methoxyglucose residue attached to the chromophore plays a determinant role in facilitating interaction of the drug with DNA/topoisomerase I complexes (Bailly et al, 1997;Rodrigues-Pereira et al, 1996). However, the exact mechanism of interaction between these compounds and DNA with or without topoisomerase I remains unclear and poorly documented.…”
mentioning
confidence: 99%
“…Considerable interest has been devoted by our laboratories to the study of correlations between the molecular structure and biochemical and/or biological activities of indolocarbazole drugs to obtain information at the molecular level that may be relevant to the proper design of chemotherapeutically more effective drugs (Rodrigues-Pereira et al, 1996;Anizon et al, 1997Anizon et al, , 1998Bailly et al, 1997Bailly et al, , 1998aPrudhomme, 1997;Moreau et al, 1998 ). The present approach has been centered on the addition of an amine group at position 2Ј (modifications at 3Ј and 4Ј positions currently are being investigated).…”
Section: Discussionmentioning
confidence: 99%
“…Indolocarbazoles linked to the carbohydrate via a ␤-glycoside linkage are potent inhibitors of topoisomerase I, whereas the ␣-analogs completely failed to inhibit the enzyme, most likely as a result of their greatly reduced affinity for DNA. Both the chemical nature and the isomeric form of the sugar residue are essential to the interaction with DNA and to the biological activity (for the structure-activity relationships, see Rodrigues-Pereira et al, 1996;Anizon et al, 1997Anizon et al, , 1998Bailly et al, 1997Bailly et al, , 1998aPrudhomme, 1997;Moreau et al, 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation